Employment and wage disparities between rural and urban areas - Sévane Ananian; Giulia Dellaferrera (International Labour Organization (ILO), 2024)
Statistical evidence from 58 countries shows that although people in rural areas are more likely to be in employment than those in urban ones, they also tend to have jobs that can put them at risk of experiencing inadequate labour protection as well as low pay. In particular, rural workers are paid, on average, 24 per cent less than their urban counterparts on an hourly basis, and only half of this gap can be explained by rural-urban discrepancies in education, job experience and occupational category. Developing countries exhibit a relatively wider gap, with the unexplained part also being larger. Furthermore, in many countries, certain groups of rural workers are at greater disadvantage, such as women, who, on average, appear to earn less than men in rural areas. However, institutional and regulatory frameworks, notably those that set minimum wages or seek to promote equal opportunities, can help to reduce labour market-related inequalities across the rural-urban divide.
Keywords: 330; decent work; rural employment; rural workers; working conditions; remuneration; low wages; inequality; data analysis